Remote interfacial electron transfer processes on nanocrystalline TiO2 sensitized with polynuclear complexes - C. A. Bignozzi; M. Alebbi; E. Costa; C. J. Kleverlaan; R. Argazzi; G. J. Meyer (International Journal of Photoenergy)
The kinetic study of interfacial electron transfer in sensitized nanocrystalline semiconductor is essential to the design of molecular devices performing specific light induced functions in a microheterogeneous environment. A series of molecular assemblies performing direct and remote charge injection to the semiconductor have been discussed in the context of artificial photosynthesis. A particular attention in this article has been paid to the factors that control the interfacial electron transfer processes in nanocrystalline TiO2 films sensitized with mononuclear and polynuclear transition metal complexes.